Pharmacological effects of Sesbania sesban: a systematic review - Walekhwa, Michael Nyongesa; Ogeto, Teresa Kerubo; Murithi, Mary Kanyiri; Malago, Zablon Lister (International Journal of Research in Medical Sciences, 2020)
The cost, side effects and imitation associated with conventional drugs have driven a substantial number of global citizens to resort to complementary medicine. Although largely informal and unregulated, the practice of herbal medicine is more engrained in low and middle income than in industrialized countries. Sesbania sesban, a plant which grows generously across most parts of the world, has been a major target by most traditional health practitioners. The effects so far reported include antimicrobial, anti-fertility, anti-diabetic, anti-inflammatory among others. No study has reviewed the scholarly works published and jointly reported results. Authros systematically reviewed papers available in different databases to give a hybrid report on the pharmacological effects of Sesbania sesban. A total of three data bases were searched using key terms like: Sesbania sesban, ethno-botany, phytochemical analysis, pharmacological effects etc. A total of 860 papers were initially recovered and further subjected to abstract and title examination which filtered them down to 40 papers. The 40 papers were assessed more against a set of criteria like: in-vivo and in-vitro studies biased to pharmacological effects of the plant, studies that were less than 15 years old and studies that used experimental design. This further scrutiny reduced the number of papers to 25. Most studies reported Sesbania sesban as having great anti-microbial, anti-fungal, anti-inflammatory and anti-diabetic qualities. No study reported any adverse effect of the plant. Authors recommend a dose-effect assessment and mechanism of action of the plant extracts especially with regard to the antimicrobial, anti-inflammatory and anti-fertility qualities.